2010
DOI: 10.1161/circinterventions.109.914051
|View full text |Cite
|
Sign up to set email alerts
|

A New Tool for the Risk Stratification of Patients With Complex Coronary Artery Disease

Abstract: on behalf of the ARTS-II InvestigatorsBackground-Presently, no effective risk model exists to predict long-term mortality or other major adverse cardiovascular and cerebrovascular events (MACCE) in those patients undergoing percutaneous coronary intervention (PCI). This study aimed to assess whether the Clinical SYNTAX Score (CSS) calculated by multiplying the SYNTAX Score to a modified ACEF score (age/ejection fraction ϩ1 for each 10 mL the creatinine clearance Ͻ60 mL/min per 1.73 m 2 ) would improve the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(90 citation statements)
references
References 29 publications
3
82
1
4
Order By: Relevance
“…1,[13][14][15][16][17][18] However, one of the most significant limitations of the SS is the omission of clinical variables in its calculation, which has been identified as a major effect in its capacity to accurately stratify patients with complex CAD. [19][20][21] The SS-II, by incorporating both the anatomic SS and clinical variables theoretically ensures a more accurate and individualized clinical outcome prediction. However, a limited number of studies have assessed the power of the SS-II.…”
Section: Discussionmentioning
confidence: 99%
“…1,[13][14][15][16][17][18] However, one of the most significant limitations of the SS is the omission of clinical variables in its calculation, which has been identified as a major effect in its capacity to accurately stratify patients with complex CAD. [19][20][21] The SS-II, by incorporating both the anatomic SS and clinical variables theoretically ensures a more accurate and individualized clinical outcome prediction. However, a limited number of studies have assessed the power of the SS-II.…”
Section: Discussionmentioning
confidence: 99%
“…It was developed during the design of SYNTAX Trial in 2009 and numerous studies confirmed its clinical validity in predicting major cardiac events (MACEs) and mortality after PCI. [19] In addition, CSS which integrates SS with modified ACEF was defined by Garg et al [9] in 2010. In this study, CSS was found a better discriminatory ability for five-year mortality and MACE than either SS alone or modified ACEF score.…”
Section: Discussionmentioning
confidence: 99%
“…The modified ACEF score was calculated using the formula: age/ejection fraction + 1 point for every 10 mL/min reduction in CrCl <60 mL/min/1.73 m² (up to a maximum of 6 points). [9] …”
Section: Syntax and Clinical Syntax Score Calculationmentioning
confidence: 99%
“…The Synergy between Percutaneous Coronary Intervention with TAXUS and Cardiac Surgery (SYNTAX) score has been used to predict clinical outcomes in patients undergoing PCI especially those with LMCA lesions and/or multivessel coronary disease based on their lesions complexity [32] . More recently, this scoring system has been integrated with some independent clinical variables such as the patient's age, creatinine serum level, and left ventricular ejection fraction (LVEF) to obtain the clinical SYNTAX score (CSS) [33] . Both scoring systems have been shown to be valid in risk stratification and early mortality prediction among older patients with ACS undergoing PCI.…”
Section: Coronary Lesions Complexitymentioning
confidence: 99%